2011
DOI: 10.1088/0953-8984/23/28/284108
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and structural analysis of polyrotaxane fibers and films

Abstract: Polyrotaxane (PR), a typical example of topological supramolecular architecture, consists of multiple cyclic molecules threaded onto a linear polymer backbone and capped with bulky end-groups. The PR system of polyethylene glycol and α-cyclodextrin (α-CD) has been extensively studied for its facile synthesis, unique molecular structure, and possible applications for various smart materials. We have previously demonstrated the fabrication of PR-based fibers without chemical cross-links by wet spinning of PR sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…9 Because a single α-CD molecule contains a large number of dipole moments (18 hydroxyl groups from six glucose units), it has been suggested that PRX-based materials could serve as piezoelectric polymers with a high number of dipole moments. 10,11 Recently, we had confirmed that a partially cross-linked PRX elastomer exhibited good piezoelectric properties and high mechanical toughness because of its partially crystallized α-CD units and partially cross-linked mobile α-CD units. 12 The hexagonally packed crystalline structures found in the noncross-linked α-CD bundle, which were attributable to the strong hydrogen bonding between the α-CD molecules, were responsible for the elastomer's piezoelectric properties.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…9 Because a single α-CD molecule contains a large number of dipole moments (18 hydroxyl groups from six glucose units), it has been suggested that PRX-based materials could serve as piezoelectric polymers with a high number of dipole moments. 10,11 Recently, we had confirmed that a partially cross-linked PRX elastomer exhibited good piezoelectric properties and high mechanical toughness because of its partially crystallized α-CD units and partially cross-linked mobile α-CD units. 12 The hexagonally packed crystalline structures found in the noncross-linked α-CD bundle, which were attributable to the strong hydrogen bonding between the α-CD molecules, were responsible for the elastomer's piezoelectric properties.…”
mentioning
confidence: 96%
“…Polyrotaxane (PRX), which is composed of α-cyclodextrin (α-CD) molecules and poly­(ethylene glycol) (PEG), is a type of supermolecule in which the ring-shaped host molecules (α-CDs) are penetrated by the linear guest molecules (PEG) . Because a single α-CD molecule contains a large number of dipole moments (18 hydroxyl groups from six glucose units), it has been suggested that PRX-based materials could serve as piezoelectric polymers with a high number of dipole moments. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5a) formed by hydrogen bonding between a-CDs. [27][28][29][30] On the other hand, all the WAXS proles of the SGC samples (Fig. 4b(ii)-(vi)) commonly showed broad humps around q ¼ 1.4 ÅÀ1 instead of the sharp crystalline peaks observed in PR; these humps, or the so-called "amorphous halo", correspond to the average structural correlation distances.…”
Section: X-ray Scatteringmentioning
confidence: 96%
“…[5][6][7] A PR consisting of poly(ethylene glycol) (PEG) as an axis and a-cyclodextrins as ring components is one of the most examined and used types of supramolecules, and has been used to create new materials such as conceptual 'slide-ring materials', [1][2][3] promising medical devices 4 and textiles with improved properties. [8][9][10][11] More recently, much attention has been focused on the synthesis, characterization and use of various PR derivatives, in which different types of functional groups were incorporated onto CD moieties to obtain a wide range of properties. [12][13][14][15][16][17][18] For example, the introduction of various functional groups on the PR resulted in solubility of the obtained derivatives in water and a wide variety of solvents, [12][13][14] in contrast to the limited solubility of the unmodified PR.…”
Section: Introductionmentioning
confidence: 99%